ANALISIS FUNGSI RUANG TERBUKA HIJAU SEBAGAI SARANA CONNECTING PEOPLE WITH NATURE DITENGAH PERKOTAAN (Studi Kasus : Tebet Eco Park Jakarta) - Maulindawati, Astrie; Khuluk, Nazaruddin (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
n urban areas, especially the city of Jakarta which is very densely populated, green openspace (Green Open Space) is urgently needed which has a function as a place to connect people withnature. However, green open spaces that already exist at several points in the city of Jakarta are infact unable to function as public spaces that are able to unite residents with nature. There are severalparks that have been revitalized, one of which is the Tebet Eco Park which is the result of therevitalization of the Honda Tebet park. To find out the successful function of Tebet Eco as a means ofconnecting humans with nature, research is needed to prove it. This study used a descriptive qualitativeresearch method. The aim of this study was to find out the success of the green open space function inthe middle of the city as a means of Connecting People With Nature seen from the various activities ofthe visitors and their supporting facilities.